Methodology of the investigation of adult-individual victimization - Sheinov, Victor P. (Journal of the Belarusian State University. Sociology, 2019)
The aim of the article was to develop a methodology and a reliable and valid test for experimental studies of the victimization of adult individuals. Similar methods and tests for adults are absent, both in domestic and in foreign literature. In the pilot study, two contrasting groups of subjects with a population of 389 and 400 people, respectively, participated in the comparison, which allowed to select the test assignments for men and women. It is proved that the constructed test satisfies the standard reliability criteria (internal consistency, reliability of test parts, retest stability); test is valid because it satisfies all known validity criteria: validation in the process of test design, validity of meaningful, «obvious», current (diagnostic), consensus, constructive, convergent, contrast, gender. The scale of the test diagnoses seven types of victimization: general and realized victimization, propensity to aggressive, self-destructive, dependent and uncritical type of victimization and the degree of insecurity of the individual from manipulation. The essence of victimization is the fact that the construct diagnosed by this test is positively correlated with the propensity to risk behavior, with anxiety, depression and low self-esteem and is negatively associated with assertiveness. Standardization of the developed test was carried out on a representative sample of more than 1000 respondents. In total, more than 1500 respondents are involved in the study.
Keywords: methodology; test; victimization; reliability; validity; risky behavior; anxiety; depression; self-esteem; assertiveness; men and women